2012
DOI: 10.1093/alcalc/ags055
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of Prepulse Inhibition of the Startle Response in Abstinent Alcoholic Male Patients

Abstract: These data suggest that sensory information processing mechanisms could be damaged in abstinent alcoholic patients. The fact that these findings are common to other psychiatric disorders could indicate the existence of a common vulnerability marker and explain the high degree of comorbidity between alcoholism and other mental illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In humans, increased ASRs have been observed in alcohol-dependent patients during acute withdrawal and in early-onset alcohol-dependent patients after protracted withdrawal [25, 36]. In contrast, other studies reported reduced ASRs in alcohol-dependent individuals during protracted abstinence [63]. These discrepant findings in both animals and humans may be attributable to procedural differences in startle assessment between laboratories (e.g., pulse intensities; assessments of the ASR under dark or light conditions) and ethanol exposure regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, increased ASRs have been observed in alcohol-dependent patients during acute withdrawal and in early-onset alcohol-dependent patients after protracted withdrawal [25, 36]. In contrast, other studies reported reduced ASRs in alcohol-dependent individuals during protracted abstinence [63]. These discrepant findings in both animals and humans may be attributable to procedural differences in startle assessment between laboratories (e.g., pulse intensities; assessments of the ASR under dark or light conditions) and ethanol exposure regimens.…”
Section: Discussionmentioning
confidence: 99%
“…PPI deficits are commonly reported in schizophrenic patients (Javitt and Freedman, 2015; Powell et al, 2012) as well as in individuals with obsessive–compulsive and panic disorder (Kohl et al, 2013). Impaired PPI has also been described in children of alcoholics (Grillon et al, 1997, 2000), heavy drinkers (Hutchison et al, 2003), and abstinent alcoholics (Marin et al, 2012). In aSI rats, PPI deficits have been observed immediately postisolation (Ko and Liu, 2015; Liu et al, 2011; Powell et al, 2015) and well into adulthood, even when aGH rats were then isolated as adults (McCool and Chappell, 2009).…”
Section: Sensory Gatingmentioning
confidence: 99%
“…A risk factor associated with the development of alcohol use disorders (AUD) is impulsivity. Recently, other neurophysiological paradigms, such as the Startle-Response Based Tasks (SRBT) and its different forms of plasticity, have been proposed as vulnerability markers for the development of alcoholism (Grillon et al, 1997;Marin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the magnitude of the SR, research related to AUD has provided varied results, with some studies demonstrating a reduction in the magnitude of the SR in heavy drinkers (Hutchison et al, 2003), in abstinent alcohol-dependent men (Marin et al, 2012) and after alcohol intake in healthy subjects (Grillon et al, 1994;Hutchison et al, 1997); and others showing an increase of the magnitude of the SR during Alcohol Withdrawal Syndrome (AWS) (Howard and Ford, 1992;Krystal et al, 1997;Schellekens et al, 2012), especially after 2 or more detoxifications (Krystal et al, 1997), in early-onset alcohol-dependent patients (Schellekens et al, 2012), and a decrease to a lesser degree compared to other clinical populations after exposure to alcohol in young men who have a parental history of alcoholism (Grillon et al, 2000). Studies based on PPI-which refers to the ability of innocuous sensory events presented before a startle-eliciting stimulus to inhibit or reduce the startle reflex (Braff et al, 1992) and which has been described as an operational measure of sensorimotor gating (Swerdlow et al, 2006)-show that it is impaired in heavy drinkers (Hutchison et al, 2003), in alcohol-dependent abstinent men (Marin et al, 2012), during AWS (Keedwell et al, 2001), in children and young adults with a family history of alcoholism (Grillon et al, 1997(Grillon et al, , 2000 and with exposure to alcohol in healthy subjects (Hutchison et al, 1997). When habituation has been studied, it has been shown that there is a decrease in children with a family history of alcoholism (Grillon et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation